Chloroplast DNA Extraction from Herbaceous and Woody Plants for Direct Restriction Fragment Length Polymorphism Analysis - C. Mariac; P. Trouslot; C. Poteaux; G. Bezançon; J.-F. Renno (BioTechniques, 2000)
The technique described here is a fast and simple method of extracting chloroplast DNA (cpDNA). It overcomes the need for differential centrifugation using density gradients. The leaves do not have to be kept in the dark and lyophilized before extraction, but lyophilization is still possible. The chloroplasts are specifically lysed in a cell extract of leaves, using a non-ionic detergent. After isolation by centrifugation, the cpDNA is purified by the combined action of proteolytic enzymes and detergents, followed by the elimination of proteins using a mixture of chloroform and isoamyl alcohol. This method provided good quality restriction profiles for all species analyzed.